Avelumab maintenance therapy for node-positive muscle invasive bladder cancer: a report of two cases - Poon, Darren M. C.; Ho, Lap Yin; Kwong, Yiu Ming (Frontiers in Oncology, 2024)
Background: Muscle-invasive bladder cancer (MIBC) with nodal involvement is associated with poor prognosis and high mortality. Treatment of node-positive MIBC is complex due to disease heterogeneity and a lack of evidence-based treatment options, especially alternatives to radical cystectomy. We describe a bladder-sparing management approach involving systemic therapy followed by maintenance therapy, illustrated with two cases of node-positive MIBC. Case presentation: Two patients with node-positive MIBC received upfront gemcitabine/cisplatin chemotherapy, concurrent chemoradiotherapy (cCRT), and avelumab (immune checkpoint inhibitor) maintenance therapy. Both patients achieved complete remission without recurrence or distant metastasis post-avelumab maintenance therapy. At the last follow-up, Patient 1 (45-year-old male) was in remission for over two years, and Patient 2 (57-year-old male) was in complete remission for over one year post-chemotherapy. Avelumab treatment was well-tolerated, with no immune-related adverse events, and quality of life (QoL) was maintained. Conclusion: Both cases showed a good response and extended remission on avelumab maintenance, supporting its use in conjunction with local consolidation therapy as a bladder-preserving approach in node-positive MIBC. Further research, such as the ongoing INSPIRE trial, is required to refine treatment strategies for this patient group.